Diversamente mendicanti: La "congregatio" di Pietro Gambacorta - Di Meglio, Rosalba (Quaderni di storia religiosa medievale, 2025)
This essay outlines the history of the hermit followers of Pietro Gambacorta, on whom historiography has focused sporadically. After presenting the complex evolution and structuring of the congregation built around Pietro, mapping the settlements of the 14th-15th centuries, it considers his story in the context of the revival of eremitism of that time, originated in Tuscany with the coming of the Olivetans and the strengthening of the Camaldolese and Servite. Back then, a series of congregations sprang up that were inspired by St. Jerome: in the case of Gambacorta and his followers, the choice to be inspired by him was strategic and meant that their movement became a privileged interpreter of a cult on which also the Friars Minor themselves, both observant and conventual, had focused.